Математическая модель индуктивного ограничителя аварийных сверхтоков трансформаторного типа - Байда, Евгений Иванович (НТУ "ХПИ", 2013)
Рассмотрена математическая модель индуктивного ограничителя аварийных сверхтоков. Описана математическая постановка задачи и приведены примеры расчета устройства ограничения тока

The mathematical model of the inductive terminator of emergency over currents is observed. The mathematical statement of problem is presented and instances of calculation of the device of restriction of the current which is based on change of resistance of the secondary winding of the transformer of a current are resulted
Keywords: выключатели с отключающей способностью; сверхток; фазные напряжения; коэффициент мощности; fault current limiter inductive; mathematical model